Strategy to Improve Student's Creativity Through Differentiated Learning Products for High School Students in Surakarta - Ambawani, Cettra Shandilia Latunusa; Harsono, Harsono; Suyatmini, Suyatmini; Haryanto, Sigit (Graduate Program Magister Manajemen Pendidikan, 2024)
The study aims to identify the increased creativity of students through product differentiation learning at Surakarta High School. The approach used in this research is quantitative. The data collection technique used is a questionnaire. The study population is all students in Class X Phase E and XI Phase F at Surakarta State High School for the academic year 2023-2024, a total of 779 students with a sample of 78 students. Each level has 39 students. Measurements using SPSS 25 with gamification of the alpha Cronbach learning media variable and student activity, normality tests, heterocadastisity tests, deviations, correlation values, and determination coefficients (R square) The collection showed that H0 was rejected and Ha received because the regression factor had a significance value < 0.05, so some suggested that there was a significant influence between the use of gamified media and activation. The results showed a regression coefficient with a significant value of 0.000, which means that there is a significant impact between learning differentiation and the product of creativity, and the determination factor (R square) is 0.370. This means that 37% of the variability in student creativity variables can be explained by product differentiation variables. The conclusion of this study is that there is a significant influence between product differentiation learning and students’ creativity in Surakarta High School by contributing to the creativity of teachers and students.